Development of applied technology textbook based on project-based learning from student’s regional potentials - Latifa, Dinda Khaira; Syahril, Syahril; Jalinus, Nizwardi; Ridwan, Ridwan (Universitas Negeri Padang, 2022)
Vocational education fully contributes to the development of Human Resources through the graduates it produces. One strategy to improve student skills in the field of appropriate technology is to apply project-based learning from regional potentials. This study aims to produce valid, practical, and effective textbooks as a tool to maximize project task-based learning from regional potential. This research was conducted using research and development methods using the ADDIE model. The validity of the textbook was obtained from the expert assessment. The data on the practicality of the textbooks were obtained from the opinion of the lecturer in charge of the course and from 30 students who took the Applied Technology Engineering course. The effectiveness of textbooks in terms of improving learning outcomes (pre-test and post-test). The results obtained from this research and development are that the textbooks are declared valid from the material and media aspects based on the assessment of experts, which are 88% and 84%, respectively. The textbooks were declared practical, the result of the lecturer's response was 86% and the student's response was 82.86%. Judging from its effectiveness, the textbook achieved a score on the Paired T-Test of 0.000 which is smaller than 0.005 which indicates a significant difference between the pre-test and post-test or there is an influence on the difference in treatment given to research subjects.